INFLUENCE OF SOCIAL MEDIA MARKETING AND ELECTRONIC WORD OF MOUTH ON BRAND LOYALTY AND PURCHASE INTENTION ON PRODUCTS SOLD VIA APPLICATION OF CONSUMERS IN BANGKOK AND ITS VICINITY - นุตะเอกวุฒิ, ชวดล; ปานคำ, สุมามาลย์; ปานคำ, สุมามาลย์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2021)
The research aimed to 1) develop the casual relationship model of the influence of social media marketing and electronic word of mouth (e-WOM) on brand loyalty and purchase intention on products sold via application of consumers in Bangkok and its vicinity, and 2) examine the consistency of the model with empirical data. The sample data was from 214 individuals who had experience in purchasing products on Lazada application by convenience sampling. The tool for data collection was online questionnaire. The statistics for data analysis were frequency, percentage, and the structural equation model. The result showed that the developed causal relationship model fitted the empirical data very well. The model’s statistics were as following: Chi-square goodness fit test (c2) = 44.22, df = 30, p-value = 0.58, CMIN/df = 1.42, GFI = 0.96, AGFI = 0.91, SRMR = 0.04, RMSEA = 0.04, and the R-square = 0.95. The model containing 4 factors, namely 1) Social Media Marketing, 2) e-WOM, 3) Brand Loyalty, and 4) Purchase Intention explained 95 percent of the variance in purchase intention on products sold via Lazada application. The result concluded that Brand Loyalty had the largest influence on Purchase Intention on products sold via Lazada application.